2009
DOI: 10.1186/1757-1626-2-7147
|View full text |Cite
|
Sign up to set email alerts
|

West nile virus myocarditis causing a fatal arrhythmia: a case report

Abstract: West Nile Virus is one of the most frequently reported etiologies of viral encephalitis in the USA. West Nile Virus infections among hospitalized patients manifests most commonly as neuro-invasive disease. West Nile Virus has also been reported to cause myocarditis. Arrhythmia is not an uncommon occurrence in viral myocarditis. As cases of West Nile Virus increase, it is important that the index of suspicion also increase for this uncommon complication. Physicians who are caring for West Nile Virus-infected pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…28 The cardiac case deserves brief comment. It was thought that this patient's abnormal liver biochemistry was due to ischaemic hepatitis, but he was found to have acute hepatitis E. This has been described with a number of other viral infections 29,30 and another similar case associated with locally acquired hepatitis E has been observed in Scotland (Ken Simpson, personal communication). Clinicians should therefore make a diagnosis of ischaemic hepatitis with caution in this context, and consider the possibility of hepatitis E infection.…”
Section: Discussionmentioning
confidence: 77%
“…28 The cardiac case deserves brief comment. It was thought that this patient's abnormal liver biochemistry was due to ischaemic hepatitis, but he was found to have acute hepatitis E. This has been described with a number of other viral infections 29,30 and another similar case associated with locally acquired hepatitis E has been observed in Scotland (Ken Simpson, personal communication). Clinicians should therefore make a diagnosis of ischaemic hepatitis with caution in this context, and consider the possibility of hepatitis E infection.…”
Section: Discussionmentioning
confidence: 77%
“…Alternatively, the ECG abnormalities may have been caused by brainstem infection, because serum creatine kinase activity was not elevated to pathological levels in infected hamsters (data not shown). The lack of overt myocarditis, evidence for skipped beats (arrhythmia), and gastrointestinal involvement may reflect the human disease in as much as cardiomyopathy is only rarely observed [44], [45], whereas GI distress is a predominant symptom of WNV infection in hospitalized patients of one study [4], and cardiac arrhythmia occurred in all groups of patients with fever, meningitis, or encephalitis in a Colorado study [9]. The implications of these cardiac data in the hamsters and in the human disease await further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cardiopulmonary manifestations were the most common complication of WNV that resulted in death [7]. Kushawaha et al [8] Our patient experienced two episodes of bradyarrhythmias resulting in code blues during his hospital stay leading to the decision to proceed with a permanent pacemaker. With aggressive cardiac intervention, our patient was able to regain cardiac stability and be transferred to a subacute facility to continue rehabilitation for his improving quadriplegia.…”
Section: Causes Of Idioventricular Rhythmmentioning
confidence: 71%